Preparation method of Z-type heterojunction composite catalyst for inducing photon-generated carrier transfer through piezoelectric polarization
By constructing a piezoelectric polarization-induced Z-type heterojunction composite catalyst, and utilizing the heterostructure of BiFeO3 and CdS nanosheets, the problems of short photogenerated carrier lifetime and limited visible light absorption were solved, achieving high-efficiency photocatalytic performance and a wide range of applications.
Patent Information
- Application Number
- CN202511306136.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-12
- Publication Date
- 2026-02-03
AI Technical Summary
Existing photocatalytic technologies suffer from short photogenerated carrier lifetimes and limited absorption of visible light, resulting in low photocatalytic efficiency and limiting their industrial application.
A piezoelectric polarization-induced Z-type heterojunction composite catalyst was constructed by using multiferroic BiFeO3 and visible light-responsive CdS nanosheets to build a Z-type heterostructure, optimize light absorption capacity and band structure, reduce interfacial resistance and photogenerated carrier recombination, and promote carrier separation and transport.
It improves the photogenerated carrier separation efficiency and interfacial charge transport rate of photocatalysts, enhances visible light response, and broadens the application range, especially showing significant catalytic efficiency in seawater catalytic hydrogen production and photothermal coupled electrocatalytic hydrogen production projects.
Smart Images

Figure CN121446522A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of energy materials, and particularly relates to a preparation method of a Z-type heterojunction composite catalyst for piezoelectric polarization-induced photogenerated carrier transfer. BACKGROUND
[0002] Semiconductor photocatalytic technology can utilize solar light or artificial light sources to realize energy conversion, and has thus become a promising technology in the field of solar energy conversion and is widely used globally. So far, although people have been trying to manufacture different visible light-driven photocatalysts, there are still problems such as short lifetime of photogenerated carriers and limited absorption of visible light, which limit the photocatalytic efficiency. In photocatalytic materials, about 90% of the photogenerated carriers generated after light excitation are rapidly complexed. This seriously limits the industrialization of photocatalytic technology. Therefore, improving the separation efficiency of photogenerated carriers is an urgent task to improve the catalytic performance of photocatalysts. To improve the photogenerated carrier separation process, it is necessary to deeply analyze the principle of photocatalytic materials in the process of solar energy action, so as to design an efficient photocatalytic solar energy conversion system, improve the photocatalytic energy conversion efficiency, and strive to realize the industrialized scale development of photocatalytic technology. Recently, research on the regulation of semiconductor photocatalytic reaction activity by external fields has gradually emerged. In photocatalytic systems with external field response performance, auxiliary microwave, temperature field or external electric field can help inhibit the recombination of photogenerated carriers and promote the reverse migration of photogenerated electrons and holes in semiconductor photocatalytic materials. In particular, polarization field engineering is gradually becoming one of the most effective strategies to improve the efficiency of photogenerated carrier separation between the bulk and the surface.
[0003] Polarity widely exists in non-centrosymmetric materials, such as piezoelectric materials, thermoelectric materials, ferroelectric materials and nonlinear optical materials. The non-centrosymmetric arrangement of atoms or atomic groups in the crystal structure of non-centrosymmetric materials (the centers of positive and negative charges do not overlap) causes the positive and negative charges to be arranged on opposite sides of the crystal structure, thereby generating a polarization electric field pointing from the negative charge region to the positive charge region. The polarization electric field appearing in the photocatalytic process can effectively promote the separation of photogenerated carriers. The polarization electric field plays a direct driving factor in some light-responsive and piezoelectric-responsive catalysts, and due to the charge shielding effect, the polarization electric field can drive the photogenerated electrons (e-) and holes (h+) to the regions with positive and negative charges, respectively. This process can make the carriers rapidly transport from the bulk to the opposite surface during the photocatalytic process, thereby realizing the spatial separation of the oxidation and reduction sites. At the same time, the polarization electric field accelerates the surface charge transfer of the photocatalyst, further improving the catalytic efficiency.
[0004] When the catalyst absorbs light of a certain wavelength range, the semiconductor catalyst is excited by light, and the electrons migrate from the valence band (VB) of the catalyst to the conduction band (CB) to form photo-generated electron-hole pairs. Photo-generated carriers will migrate from the bulk phase to the catalytically active sites on the surface of the catalyst, and participate in redox reactions, which usually requires several hundred picoseconds. However, the recombination of photo-generated carriers in the bulk phase only takes a few picoseconds, which is one hundredth of the carrier migration. Improving the utilization rate of photo-generated carriers in chemical reactions is another key to improving the photocatalytic performance. By constructing a band-matched heterojunction photocatalyst through the difference in the energy band structure of different semiconductors, a spontaneous internal electric field can be formed at the composite interface by utilizing the potential difference, realizing the spontaneous movement of photo-generated carriers from high energy level to low energy level, and further becoming an effective strategy to improve the carrier separation efficiency of photocatalysts. SUMMARY
[0005] In order to overcome the shortcomings of the prior art, the present application provides a preparation method of a Z-type heterojunction composite catalyst for piezoelectric polarization induced photo-generated carrier transfer, which utilizes multi-ferroelectric BiFeO3 and visible light responsive CdS nanosheets to construct a Z-type heterojunction with active electron transport characteristics. Not only the light absorption capacity and the energy band structure are optimized, but also the interface resistance and the recombination of photo-generated carriers are reduced. The combination of BiFeO3 particles and ultra-thin CdS not only inhibits the agglomeration of CdS nanosheets, but also helps to improve the specific surface area of the reaction system. The present application utilizes multi-ferroelectric BiFeO3 and visible light responsive CdS nanosheets to construct a Z-type heterojunction with active electron transport characteristics. The construction of this active electron transport system promotes the separation and transport of carriers, providing a new strategy for improving the photocatalytic hydrogen production reaction activity.
[0006] The technical scheme adopted by the present application to solve its technical problems is as follows:
[0007] Step 1: In a beaker, add bismuth salt, iron salt and solvent according to the stoichiometric ratio; then water bath constant temperature stirring to obtain a pre-prepared precursor solution; continuously stir the precursor solution, and gradually add nitric acid until the bismuth salt and iron salt are completely dissolved; add a moderate amount of complexing agent according to the stoichiometric ratio to the precursor solution, and continuously stir to obtain a precursor gel; place the precursor gel in a muffle furnace to calcine to form a catalyst powder;
[0008] Step 2: Add a stoichiometric amount of cadmium chloride solution to a sodium citrate solution and stir at room temperature; then, add 3mL of concentrated ammonia NH3·H2O and 10mL of 0.6M thiourea solution in sequence; after natural cooling, centrifugal collection of the precipitate, and washing with deionized water and anhydrous ethanol several times to remove impurities, then drying in an oven at 60℃ to obtain CdS nanosheets;
[0009] Step 3: The stoichiometric ratio of BiFeO3 was weighed and added into the sodium citrate solution, and 0.3M cadmium chloride solution was added in different volumes according to 10wt%, 20wt% and 30wt%, respectively, and stirred for 20min; then 3mL of concentrated ammonia water NH3·H2O and different volumes of 0.6M thiourea solution were added in turn, and reacted in a 60℃ water bath for 2.5 hours; after natural cooling, the precipitate was collected by centrifugation, rinsed with deionized water and anhydrous ethanol several times, and then dried in a 60℃ oven, to obtain 10% CdS / BiFeO3, 20% CdS / BiFeO3 and 30% CdS / BiFeO3 samples, respectively.
[0010] Preferably, the bismuth salt is soluble bismuth nitrate, and the iron salt is soluble ferric nitrate.
[0011] Preferably, the complexing agent includes any one of citric acid, ethylenediaminetetraacetic acid, and triammonium citrate.
[0012] Preferably, the complexing agent is triammonium citrate.
[0013] Preferably, the solvent includes at least one of dilute nitric acid, ammonia water and deionized water.
[0014] Preferably, the solvent is dilute nitric acid.
[0015] Preferably, in step 1, the calcination temperature is 500-700℃.
[0016] Preferably, in step 1, the calcination temperature is 550℃, the calcination time is 2 hours, the heating rate is 1-5℃·min -1 , and the cooling rate is 1-5℃·min -1 .
[0017] Preferably, the molar ratio of the bismuth salt to the iron salt is 10-12:1.
[0018] Preferably, the molar ratio of the bismuth salt to the iron salt is 11:1, and the ratio of the bismuth salt to nitric acid and the complexing agent is 1mol:30mL:0.2mol.
[0019] The beneficial effects of the present application are as follows:
[0020] First, the present application proposes a Z-type heterojunction composite catalyst for piezoelectric polarization-induced photogenerated carrier transfer, as well as a preparation method and application thereof. The CdS / BiFeO3 Z-type heterojunction composite catalyst optimizes the multiferroicity of the BiFeO3-based material through the construction of CdS nanosheets. At the same time, the construction of the composite material enhances the visible light absorption capacity and the charge transfer rate between the two components. The constructed Z-type heterojunction reduces the recombination of photogenerated carriers, improves the interface charge transport, and increases the adsorption and desorption rate of the reaction medium.
[0021] Secondly, the Z-type heterojunction composite catalyst for piezoelectric polarization induced photogenerated carrier transfer provided by the application not only has visible light response, but also has good piezoelectricity. The double internal electric field coupling of the Z-type heterojunction and the piezoelectric polarization electric field enhance the mobility of the bulk free charge and the photogenerated carrier. The photo-piezoelectric catalytic efficiency of the composite material is obviously higher than the sum of the hydrogen produced by the piezoelectric reaction and the photocatalytic reaction.
[0022] Thirdly, the Z-type heterojunction composite catalyst for piezoelectric polarization induced photogenerated carrier transfer provided by the application can be applied to seawater catalytic hydrogen production, photo-thermal coupling electrocatalytic hydrogen production engineering and the like. Compared with the existing electrolytic hydrogen production, the application range is wider. BRIEF DESCRIPTION OF DRAWINGS
[0023] Figure 1 is the preparation flowchart of the single-phase BiFeO3, CdS and the composite material of the application, (a) is single-phase BiFeO3, (b) is CdS, and (c) is the composite material;
[0024] Figure 2 is the scanning electron microscope image of the alkali metal doped fluorite catalyst of the application, wherein (a) is the original BiFeO3, (b) is the original CdS, (c) is 10% CdS / BiFeO3, (d) is 20% CdS / BiFeO3, (e) is 30% CdS / BiFeO3 heterojunction composite material, and (f) is 20% CdS / BiFeO3.
[0025] Figure 3 is the cumulative H2 evolution reaction time and hydrogen production rate of the original BiFeO3, the original CdS and the CdS / BiFeO3 composite catalyst with the Na2S / Na2SO3 mixed solution as a sacrificial reagent, (a) and (b) are under visible light irradiation, (c) and (d) are under ultrasonic vibration, (e) and (f) are under ultrasonic vibration and visible light irradiation, (g) and (h) are under ultrasonic vibration and visible light irradiation in pure water, and (i) is the catalytic stability test of the original CdS and 20% CdS / BiFeO3 under ultrasonic vibration and visible light irradiation with a sacrificial agent. DETAILED DESCRIPTION
[0026] The application will be further described below in combination with the drawings and examples.
[0027] The present application aims at the defects of poor hydrogen production efficiency, insufficient reaction active site and serious photogenerated carrier recombination of the catalyst based on ferroelectric material in the existing photocatalytic technology, and provides a preparation method of a Z-type heterojunction composite catalyst with piezoelectric polarization induced photogenerated carrier transfer, a Z-type heterostructure with active electron transport characteristics is constructed by using multiferroic BiFeO3 and visible light responsive CdS nanosheet, which not only optimizes the light absorption capacity and energy band structure, but also reduces the interface resistance and photogenerated carrier recombination, the combination of BiFeO3 particles and ultra-thin CdS not only inhibits the agglomeration of CdS nanosheet, but also helps to improve the specific surface area of the reaction system. And the CdS nanosheet structure as a reducing phase is conducive to proton adsorption and hydrogen desorption, and the combination of the multi-physical field of light radiation and environmental vibration change obtains a photo-piezoelectric catalyst with excellent catalytic activity and stability.
[0028] The technical purpose of the present application is achieved by the following technical scheme:
[0029] As Figure 1 A preparation method of a Z-type heterojunction composite catalyst with piezoelectric polarization induced photogenerated carrier transfer, comprising the steps of:
[0030] Step 1, a beaker is added with bismuth salt, iron salt and an appropriate amount of solvent according to the stoichiometric ratio, and then a pre-prepared precursor solution is obtained by constant temperature stirring in a water bath. Stir the precursor solution continuously, and gradually add nitric acid until the bismuth salt and iron salt are completely dissolved. A complexing agent is added to the precursor solution in a moderate stoichiometric ratio, and the precursor gel is obtained by continuous stirring. The precursor gel is placed in a muffle furnace at 550 DEG C for 2 hours to form a catalyst powder;
[0031] Step 2, a stoichiometric amount of cadmium chloride solution is added to a sodium citrate solution and stirred at room temperature. Then, 3mL of concentrated ammonia (NH3·H2O) and 10mL of 0.6M thiourea solution are added in turn. After natural cooling, the precipitate is collected by centrifugation, washed with deionized water and anhydrous ethanol several times to remove impurities, and then dried in an oven at 60 DEG C to obtain CdS nanosheet;
[0032] Step 3, a stoichiometric amount of BiFeO3 is weighed and added to a sodium citrate solution, and 0.3M cadmium chloride solution is added in different volumes according to 10wt%, 20wt% and 30wt%, respectively, and stirred for 20min. Then 3mL of concentrated ammonia (NH3·H2O) and different volumes of 0.6M thiourea solution are added in turn, and the reaction is carried out in a 60 DEG C water bath for 2.5 hours. After natural cooling, the precipitate is collected by centrifugation, washed with deionized water and anhydrous ethanol several times, and then dried in an oven at 60 DEG C to obtain 10% CdS / BiFeO3, 20% CdS / BiFeO3 and 30% CdS / BiFeO3 samples, respectively.
[0033] BiFeO3 and CdS have piezoelectric effect that can induce spontaneous polarization moment under external force. The introduction of polarization factor can enhance the driving force of charge separation in the bulk phase, thereby forming an internal electric field. The photo-generated electron-hole pairs in the photocatalytic process migrate to the surface of different polar regions under the influence of the internal electric field. The piezoelectric polarization process significantly enhances the characteristics of charge redistribution in the bulk phase of the catalyst and induces effective separation of photo-generated carriers, which further migrate to the interface through Z-type heterojunction.
[0034] The bismuth salt is soluble bismuth nitrate; the iron salt is soluble ferric nitrate; the complexing agent includes any one of citric acid, ethylenediaminetetraacetic acid, and triammonium citrate; and the solvent includes at least one of dilute nitric acid, ammonia water, and deionized water.
[0035] In step 1, the calcination temperature is selected to be 550 DEG C, the calcination time is 2 hours, the heating rate is 1-5 DEG C·min -1 , and the cooling rate is 1-5 DEG C·min -1 .
[0036] The molar ratio of the bismuth salt and the iron salt is 11:1, the ratio of the bismuth salt, nitric acid, and the complexing agent is 1 mol:30 mL:0.2 mol, and the stirring time is 4-10 hours.
[0037] The piezoelectric photocatalytic reaction technology is adopted, and the photo-generated electron-hole pairs in the photocatalytic process migrate to the surface of different polar regions under the influence of the internal electric field. The piezoelectric polarization process significantly enhances the characteristics of charge redistribution in the bulk phase of the catalyst and induces effective separation of photo-generated carriers, which further migrate to the interface through Z-type heterojunction, fully utilizes the light response and piezoelectric response of the Z-type heterojunction composite material of the ultra-thin CdS nanolayer coated BiFeO3, and realizes multi-field coupling energy conversion optimization and application scenario widening.
[0038] This invention utilizes piezoelectric semiconductor photocatalysts, ambient temperature difference, and solar energy for catalytic water splitting to produce hydrogen, employing a green and sustainable energy chemical conversion method. The piezoelectric photocatalytic water splitting hydrogen production technology uses a piezoelectric semiconductor material with a suitable band structure to convert absorbed photons into photoexcitons. These photoexcitons separate into charge carriers (electrons and holes), which are transported to the catalyst surface and undergo redox reactions with water to produce hydrogen and oxygen. Simultaneously, external vibrational changes drive changes in the electric dipoles within the piezoelectric material. With changes in the intrinsic crystal structure, the non-zero dipole moment formed in the lattice induces a polarization potential, resulting in negative and positive charges distributed on both sides of the piezoelectric material. On one hand, electrons transfer from molecular orbitals to the conduction band. On the other hand, electrons leave the valence band and transfer to the lowest unoccupied molecular orbitals. The internal potential acts as a bias to change the energy of the surface charge, and the occurrence of various reactions depends on whether the electronic energy levels meet the energy requirements of the desired electrochemical reaction (redox reaction potential). Due to the relative displacement of positive and negative charges, the piezoelectric material polarizes under stress and strain. When the surface has a sufficiently high Gibbs free energy, such polarized materials will undergo interfacial redox reactions.
[0039] Example 1:
[0040] Construct a 10% CdS / BiFeO3Z-type heterojunction composite catalyst.
[0041] Weigh 0.011 mol Bi(NO3)3 and 0.01 mol Fe(NO3)3·9H2O, and dissolve them separately in 100 mL of deionized water to obtain 0.11 M bismuth nitrate and 0.1 M ferric nitrate aqueous solutions. While stirring continuously in the bismuth nitrate solvent, gradually add 3 mL of nitric acid (68%) until the bismuth nitrate is completely dissolved. Then mix the two solutions, add 0.02 mol of triammonium citrate as a complexing agent, stir for 30 min, and continue stirring at 90 °C until the water is completely evaporated to obtain a reaction intermediate gel. Calcine the gel at 550 °C for 2 h to obtain pure phase BiFeO3 powder particles. Weigh 0.5 g of BiFeO3 and add it to 50 mL of 0.1 M sodium citrate solution, then add 0.3 M cadmium chloride solution at 10 wt%, and stir for 20 min. Then add 3 mL of concentrated ammonia and 0.6 M thiourea solution, and react in a 60 °C water bath for 2.5 h. After natural cooling, the precipitate was collected by centrifugation, rinsed several times with deionized water and anhydrous ethanol, and then dried in an oven at 60°C to obtain a 10% CdS / BiFeO3 sample.
[0042] The morphology of the 10% CdS / BiFeO3 sample is as follows: Figure 2 As shown in (c), the grain surface is smooth, and no impurity phases are formed. The hydrogen production activity diagram is as follows: Figure 3 As shown.
[0043] Example 2:
[0044] Construct a 20% CdS / BiFeO3Z-type heterojunction composite catalyst.
[0045] Weigh 0.011 mol Bi(NO3)3 and 0.01 mol Fe(NO3)3·9H2O, and dissolve them separately in 100 mL of deionized water to obtain 0.11 M bismuth nitrate and 0.1 M ferric nitrate aqueous solutions. While stirring continuously in the bismuth nitrate solvent, gradually add 3 mL of 68% nitric acid until the bismuth nitrate is completely dissolved. Then mix the two solutions, add 0.02 mol of triammonium citrate as a complexing agent, stir for 30 min, and continue stirring at 90 °C until the water is completely evaporated to obtain a reaction intermediate gel. Calcine the gel at 550 °C for 2 h to obtain pure phase BiFeO3 powder particles. Weigh 0.5 g of BiFeO3 and add it to 50 mL of 0.1 M sodium citrate solution, then add 0.3 M cadmium chloride solution at 20 wt%, and stir for 20 min. Then add 3 mL of concentrated ammonia and 0.6 M thiourea solution, and react in a 60 °C water bath for 2.5 h. After natural cooling, the precipitate was collected by centrifugation, rinsed several times with deionized water and anhydrous ethanol, and then dried in an oven at 60°C to obtain a 20% CdS / BiFeO3 sample.
[0046] The morphology of the 20% CdS / BiFeO3 sample is as follows: Figure 2 As shown in (d) and 2(f), the grain surfaces are smooth and no impurity phases are formed. The hydrogen production activity diagram is as follows: Figure 3 As shown.
[0047] Example 3:
[0048] Construct a 30% CdS / BiFeO3Z-type heterojunction composite catalyst.
[0049] Weigh 0.011 mol Bi(NO3)3 and 0.01 mol Fe(NO3)3·9H2O, and dissolve them separately in 100 mL of deionized water to obtain 0.11 M bismuth nitrate and 0.1 M ferric nitrate aqueous solutions. While stirring continuously in the bismuth nitrate solvent, gradually add 3 mL of nitric acid (68%) until the bismuth nitrate is completely dissolved. Then mix the two solutions, add 0.02 mol of triammonium citrate as a complexing agent, stir for 30 min, and continue stirring at 90 °C until the water is completely evaporated to obtain a reaction intermediate gel. Calcine the gel at 550 °C for 2 h to obtain pure phase BiFeO3 powder particles. Weigh 0.5 g of BiFeO3 and add it to 50 mL of 0.1 M sodium citrate solution, then add 0.3 M cadmium chloride solution at 30 wt%, and stir for 20 min. Then add 3 mL of concentrated ammonia and 0.6 M thiourea solution, and react in a 60 °C water bath for 2.5 h. After natural cooling, the precipitate was collected by centrifugation, rinsed several times with deionized water and anhydrous ethanol, and then dried in an oven at 60°C to obtain a 20% CdS / BiFeO3 sample.
[0050] The morphology of the 30% CdS / BiFeO3 sample is as follows: Figure 2 As shown in (e), the grain surface is smooth, and no impurity phases are formed. The hydrogen production activity diagram is as follows: Figure 3 As shown.
[0051] from Figure 2 As shown in (a), the synthesized BiFeO3 particles are distributed in the range of 100-300 nm, with a smooth surface and spindle-shaped and elliptical particle shapes. The particles are interwoven, forming numerous porous structures, which helps increase the contact area between the material and other catalyst phases in the reaction solution, effectively improving the adsorption effect. The morphology and structure of the original CdS were also analyzed, such as... Figure 2 As shown in (b), CdS is a nanoflower structure assembled from two-dimensional nanosheets, with the thickness of a single nanosheet on the nanometer scale. The nanoflowers formed by the curling of multiple nanosheets greatly increase the contact area with the reaction solution, and the ultrathin sheet structure also helps to shorten the charge migration path from the bulk phase to the active sites on the catalyst surface. Figure 2 Images (c)-(e) are scanning electron microscope (SEM) images of CdS / BiFeO3 composite samples where CdS nanosheets are gradually coated onto the surface of BiFeO3 particles. With increasing CdS mass fraction, 20% CdS / BiFeO3 not only has a larger contact area than 10% CdS / BiFeO3, but also inhibits CdS aggregation, resulting in better dispersibility. However, when the CdS mass fraction is too high, the CdS nanosheets in the 30% CdS / BiFeO3 surface exhibit some aggregation and no longer spread out as much as in 20% CdS / BiFeO3, which may adversely affect mass transfer in the reaction system.
[0052] Figure 3 (a) and (b) show the hydrogen production rate and yield under pure light conditions for pristine BiFeO3, pristine CdS, and CdS / BiFeO3 heterojunction composites with different mass ratios. The pristine BiFeO3, limited by its large grain size, suffers from poor carrier transport in the bulk phase, resulting in unsatisfactory hydrogen production performance. In contrast, the pristine CdS phase, with its thin-layer structure and high specific surface area, accelerates the transport of photogenerated carriers, which is beneficial for both reactant adsorption and hydrogen desorption, thus achieving a hydrogen production rate of 0.54 mmol·g under visible light irradiation. -1 ·h -1 All composite materials exhibited higher hydrogen production rates than the original BiFeO3 and CdS, with the hydrogen evolution rate of 20% CdS / BiFeO3 reaching 1.31 mmol·g⁻¹. -1 ·h -1 The efficiency of photocatalytic hydrogen production was 42.81 times higher than that of the original BiFeO3. This not only confirms that its photocatalytic performance is related to its specific surface area and the separation efficiency of photogenerated electron-hole pairs, but also demonstrates that the heterojunction structure formed between BiFeO3 and CdS can effectively accelerate the separation of photogenerated carriers. To further confirm the piezoelectric response and piezoelectric catalytic efficiency of each sample, ultrasound was introduced as an external piezoelectric field to conduct piezoelectric catalytic hydrogen production experiments. The results are as follows: Figure 3 As shown in (c) and (d), the difference in hydrogen production rate between piezoelectric and photocatalysis is no longer significant, but the catalytic activity of the composite sample is much higher than that of the pure phase sample. Furthermore, the spindle-shaped and elliptical particle structure of the original BiFeO3 results in a deformation frequency and degree much lower than that of the two-dimensional sheet structure of CdS, leading to its relatively low piezoelectric catalytic activity. When each catalyst sample is simultaneously irradiated with visible light and subjected to ultrasound, the catalytic activity of each sample is much higher than the sum of photocatalysis and piezoelectric catalysis. This indicates that the coupling process of piezoelectric effect and photocatalysis forms a synergistic effect. Specifically, under multi-field coupling, the hydrogen production rate of 20% CdS / BiFeO3 can reach 3.58 mmol·g⁻¹. -1 ·h -1 In order to expand the application scope of catalytic hydrogen production, Figure 3 (g) and (h) show the hydrogen evolution amount and rate of pure water splitting under coupled photo-piezoelectric catalysis for each catalyst. In the initial stage of the multi-field coupled catalytic pure water splitting reaction, the reaction rate is relatively slow due to the limitation of the four-electron reaction at the oxidation terminal. However, the reaction rate increases significantly after 2 hours, with the hydrogen production rate of 20% CdS / BiFeO3 reaching 0.19 mmol·g. -1 ·h -1 .
[0053] The spontaneous polarization of the catalyst induced by the external piezoelectric field generates an internal polarization electric field within the grains. Under the influence of this internal electric field, free charges within the grains migrate towards the interface between the two components. Another internal electric field generated between the two components leads to a heterojunction, further facilitating the migration of photogenerated charges into the bulk phase. Conversely, the dual internal electric field constructed by multi-field coupling and the heterostructure effectively suppresses the recombination of photogenerated carriers, thus enabling the composite catalyst to separate pure water. Furthermore, the composite morphology of CdS nanosheets supported on the BiFeO3 surface exhibits a rougher surface and a richer pore structure. Under the ultrasonic-driven rinsing of the reaction system, the interfacial mass transfer efficiency of the catalyst is effectively improved, thereby significantly enhancing the reactivity of photo-piezoelectric hydrogen production.
[0054] The chemical stability of photocatalytic redox reactions is a long-standing and unavoidable topic. Due to the stable peroxide crystal structure of BiFeO3, it possesses good chemical stability; conversely, the easily photocorroded CdS has been used for comparison with 20% CdS / BiFeO3. The catalytic stability tests of pristine CdS and 20% CdS / BiFeO3 with the sacrificial agent under coupled ultrasonic vibration and visible light irradiation conditions are as follows: Figure 3 As shown in (i), the 20% CdS / BiFeO3 exhibits excellent chemical stability in all three cycles, while the hydrogen production activity of the original CdS shows some decline. This is because the relative energy levels at the heterojunction interface determine the direction and efficiency of carrier separation. Furthermore, the heterostructure reduces the necessary charge migration distance and spatially separates electron-hole pairs, effectively suppressing bulk phase recombination. In contrast, the original CdS is easily oxidized by photogenerated holes, leading to self-corrosion. Constructing a Z-shaped heterojunction allows BiFeO3 to capture photogenerated holes, thereby improving the stability of the composite material. Compared to the sacrificial system, pure water splitting is thermodynamically more difficult and kinetically slower. The hydrogen production cycle stability of the original CdS separating pure water is much lower than that of the sacrificial system, indicating that using Na2S / Na2SO3 as a sacrificial agent can reduce the thermodynamic barrier to H2O separation and decrease the photocorrosion of the catalyst.
Claims
1. A method for preparing a Z-type heterojunction composite catalyst with piezoelectric polarization-induced photogenerated carrier transfer, characterized in that, Includes the following steps: Step 1: Add the bismuth salt, iron salt, and solvent weighed according to the stoichiometric ratio to a beaker; then stir in a water bath at a constant temperature to obtain a pre-prepared precursor solution; continuously stir the precursor solution and gradually add nitric acid until the bismuth salt and iron salt are completely dissolved; add a complexing agent with an appropriate stoichiometric ratio to the precursor solution and continue stirring to obtain a precursor gel. The precursor gel was calcined in a muffle furnace to form catalyst powder. Step 2: Add the cadmium chloride solution weighed according to the stoichiometric ratio to the sodium citrate solution and stir at room temperature; then, add 3 mL of concentrated ammonia (NH3·H2O) and 10 mL of 0.6 M thiourea solution in sequence; after natural cooling, centrifuge to collect the precipitate, wash several times with deionized water and anhydrous ethanol to remove impurities, and then dry in an oven at 60 °C to obtain CdS nanosheets. Step 3: Weigh out BiFeO3 in stoichiometric proportions and add it to sodium citrate solution. Add different volumes of 0.3M cadmium chloride solution at 10wt%, 20wt%, and 30wt%, respectively, and stir for 20 min. Then, add 3 mL of concentrated ammonia (NH3·H2O) and different volumes of 0.6M thiourea solution sequentially, and react in a 60℃ water bath for 2.5 hours. After natural cooling, centrifuge to collect the precipitate, wash it several times with deionized water and anhydrous ethanol, and then dry it in a 60℃ oven to obtain 10% CdS / BiFeO3, 20% CdS / BiFeO3, and 30% CdS / BiFeO3 samples, respectively.
2. The method for preparing a Z-type heterojunction composite catalyst with piezoelectric polarization-induced photogenerated carrier transfer according to claim 1, characterized in that, The bismuth salt is soluble bismuth nitrate, and the iron salt is soluble ferric nitrate.
3. The method for preparing a Z-type heterojunction composite catalyst with piezoelectric polarization-induced photogenerated carrier transfer according to claim 1, characterized in that, The complexing agent includes any one of citric acid, ethylenediaminetetraacetic acid, and triammonium citrate.
4. The method for preparing a Z-type heterojunction composite catalyst with piezoelectric polarization-induced photogenerated carrier transfer according to claim 1, characterized in that, The complexing agent is triammonium citrate.
5. The method for preparing a Z-type heterojunction composite catalyst with piezoelectric polarization-induced photogenerated carrier transfer according to claim 1, characterized in that, Preferably, the solvent includes at least one of dilute nitric acid, ammonia, and deionized water.
6. The method for preparing a Z-type heterojunction composite catalyst with piezoelectric polarization-induced photogenerated carrier transfer according to claim 1, characterized in that, The solvent sample was dilute nitric acid.
7. The method for preparing a Z-type heterojunction composite catalyst with piezoelectric polarization-induced photogenerated carrier transfer according to claim 1, characterized in that, In step 1, the calcination temperature is 500–700°C.
8. The method for preparing a Z-type heterojunction composite catalyst with piezoelectric polarization-induced photogenerated carrier transfer according to claim 1, characterized in that, In step 1, the calcination temperature is 550℃, the calcination time is 2 hours, and the heating rate is 1-5℃·min. -1 The cooling rate is 1–5 °C / min. -1 .
9. The method for preparing a Z-type heterojunction composite catalyst with piezoelectric polarization-induced photogenerated carrier transfer according to claim 1, characterized in that, The molar ratio of bismuth salt to iron salt is 10 to 12:
1.
10. The method for preparing a Z-type heterojunction composite catalyst with piezoelectric polarization-induced photogenerated carrier transfer according to claim 1, characterized in that, The molar ratio of bismuth salt to iron salt is 11:1; the ratio of bismuth salt to nitric acid and complexing agent is 1 mol: 30 mL: 0.2 mol.
